Perspectives and preferences for a mobile health tool designed to facilitate HPV vaccination among young men who have sex with men. Issue 7 (3rd August 2019) - Fontenot, Holly B.; Rosenberger, Joshua G.; McNair, Katelyn T.; Mayer, Kenneth H.; Zimet, Gregory
ABSTRACT: We sought to understand young men who have sex with men (YMSM) perspectives and preferred features for a mobile health (mHealth) tool designed to facilitate human papillomavirus (HPV) vaccination. YMSM were recruited on a popular social/sexual networking app to participate in online focus groups. Discussions were designed to elicit what the men would want in a mHealth tool specific for sexual health and HPV. Demographic data were analyzed using descriptive statistics and focus group data were analyzed using conventional content analysis. Forty-eight YMSM participated. Mean age was 23.4 years, and 70.0% reported their race as Black. Qualitative themes included general HPV knowledge and awareness, current patterns in technology use, desired app qualities, and desired app content. Youth described varying levels of HPV knowledge, utilized apps to engage socially, and for travel, banking, gaming, news and entertainment, and few used apps to facilitate personal health or engage with healthcare systems. Participants desired credible, relatable, secure, and easy to use interfaces that provided sexual health and HPV information in a positive context. They described ways to creatively engage and directly connect youth to health providers. We identified a culturally relevant youth driven approach to facilitate HPV vaccination and sexual health among YMSM.